234k views
4 votes
Let f(x) = 8x3 − 22x2 − 4 and g(x) = 4x − 3. Find f of x over g of x.

2x2 − 4x − 3 − 13 over quantity 4x minus 3
2x2 − 4x − 3 − quantity of 4 x minus 3 over 13
2x2 − 7x − 1
2x2 − 7x − 5 + quantity of x minus 4 over quantity of 4 x minus 3

User Xiaofan Hu
by
6.0k points

2 Answers

5 votes

Given that
f(x)=8x^3-22x^2-4 and
g(x)=4x-3

Question says to find f of x over g of x which simply means divide value of f(x) by value of g(x)

Dividing them gives:


(f(x))/(g(x))=(8x^3-22x^2-4)/(4x-3)

Denominator is already in factored form which can't divide numerator means it can't be simplified more.

Hence final answer is
(f(x))/(g(x))=(8x^3-22x^2-4)/(4x-3).

other part of question is not clear so i will skip them.

User Bartosz Gajda
by
6.4k points
5 votes

Answer:

The correct answer is the first one.

Explanation:

We have the functions
f(x) = 8x^3-22x^2-4 and
g(x) = 4x-3. Then, the fraction is


(f(x))/(g(x)) = (8x^3-22x^2-4)/(4x-3).

If we want to give a ‘‘simplified’’ expression for this quotient we must do a a division of polynomials. The algorithm is the analogue for the division of integers. Attached there is an image of the procedure.

After the completion of the division algorithm we obtain


(f(x))/(g(x)) = ((4x-3)(2x^2-4x-3)-13)/(4x-3) = 2x^2-4x-3 - (13)/(4x-3).

Let f(x) = 8x3 − 22x2 − 4 and g(x) = 4x − 3. Find f of x over g of x. 2x2 − 4x − 3 − 13 over-example-1
User Sergio Moura
by
5.2k points